2019
DOI: 10.3390/ijerph16245053
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet Use and Smoking among Chinese Junior Secondary Students: The Mediating Role of Depressive Symptomatology and Family Support

Abstract: Background: Internet use is significant public health issue and can be a risk factor for other addictive behaviors, such as smoking. The present study examined the association between problematic Internet use (PIU) (i.e., Internet addiction (IA) and social networking addiction (SNA)) and smoking, and the mediating role of depressive symptomatology and family support played in such associations. Methods: A cross-sectional study was conducted among 5182 junior secondary students (grade 7 and 8) recruited from ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
4
0
1
Order By: Relevance
“…As for the conceptualisation of well-being in relation to DTNU, the literature has largely addressed psychological individual dimensions with most studies focussing on depression and anxiety. Also, if some social and contextual dimensions have been considered (e.g., Mo et al, 2019 ; Mikuška et al, 2020 ), there is a neglect of studies that have included learning difficulties and school attainment variables. The relation between DTU and well-being is anything but simple and unidirectional: a higher number of studies considered well-being dimensions as predictors of DTNU; nonetheless, consistent studies have shown that DTNU can also contribute to the development of psychological problems.…”
Section: Discussionmentioning
confidence: 99%
“…As for the conceptualisation of well-being in relation to DTNU, the literature has largely addressed psychological individual dimensions with most studies focussing on depression and anxiety. Also, if some social and contextual dimensions have been considered (e.g., Mo et al, 2019 ; Mikuška et al, 2020 ), there is a neglect of studies that have included learning difficulties and school attainment variables. The relation between DTU and well-being is anything but simple and unidirectional: a higher number of studies considered well-being dimensions as predictors of DTNU; nonetheless, consistent studies have shown that DTNU can also contribute to the development of psychological problems.…”
Section: Discussionmentioning
confidence: 99%
“…The associations of adolescent smoking behaviour with familial or parental variables have been extensively examined [ 44 , 45 , 46 , 47 ]. Although various variables to describe family functioning and parenting have received a great deal of attention [ 15 , 48 ], in this study we focussed on the associations of current smoking with family support.…”
Section: Discussionmentioning
confidence: 99%
“…Ancak alkol ve sigara gibi kısa süreli rahatlama sağlayan maddelerin internet ve sosyal medya kullanımında pekiştireç rolü oynadığını ve risk faktörleri olduğunu gösteren çok sayıda çalışma bulgusu bulunmaktadır (32). Ayrıca problemli internet kullanımının özellikle sigara kullanımı için bir risk faktörü olduğunu vurgulanmaktadır (33,34). Bizim araştırmamızda da oyun bağımlılığı ile sigara ve alkol kullanımı arasında ilişki olduğu tespit edildi.…”
Section: Bulgularunclassified